CINTA TANAH AIR DALAM PERSPEKTIF PARTAI POLITIK - Harry Safari Margapradja (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2018)
The homeland is a strong nature and becomes the character of every human being.Separating from the homeland or even the hometown feels heavy and tormenting. In Tafsiral-Kabir, Juz XV, p. 165; al-Imam Fakhr Al-Din al-Razi said that; "Allah made leaving hishomeland equal to suicide". Al-Razi's statement implies that leaving the homeland topeople of understanding is a very difficult and difficult matter, just as the suicidal illness.So, the love of the homeland is a very deep nature in the human soul. Political parties inthe world of politics, especially in local politics will be easily understood by firstunderstanding the definition of political parties. There are three theories that try to explainthe origin of political parties.Keywords: The Homeland, Political Parties, PDIP